2015
DOI: 10.1016/j.eats.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Correction of a Supracondylar Malunion in a Child

Abstract: Malunions are a well-recognized complication of pediatric supracondylar humeral fractures. Results of corrective osteotomies vary, and complication rates have been reported to be as high as 40%. Considering the high rate of complications for malunion correction, we investigated the feasibility of arthroscopy. We present a technique for arthroscopic supracondylar osteotomy and percutaneous pinning. There are many advantages of an arthroscopic approach to malunion correction, including extension-type deformity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…At the same time, several methods have been described. The cross-wired and lateral wires configurations are the most examined [ 3 , 24 , 25 , 26 , 27 , 28 ]: cross-wired is more biomechanically stable [ 26 , 27 ], lateral reduces nerve injury risk [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, several methods have been described. The cross-wired and lateral wires configurations are the most examined [ 3 , 24 , 25 , 26 , 27 , 28 ]: cross-wired is more biomechanically stable [ 26 , 27 ], lateral reduces nerve injury risk [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malunion is a complication of SCHF treatment that occurs during an arthroscopic approach. Koehler et al [21] showed that arthroscopy is useful and favorable and offers deformity correction and safe access of the anterior humerus as well as minimal dissection, scarring and intracapsular contractures.…”
Section: Discussionmentioning
confidence: 99%
“…Though lateral condyle fractures (LCFs) are the most common fracture addressed arthroscopically in the pediatric population, the orthopedic literature also describes techniques for fixation of coronoid, supracondylar, medial epicondyle, radial head or neck fractures. 8,11,13,17,[21][22][23] Fractures of the lateral condyle are the second most common pediatric elbow fracture, and represent a diagnostic and treatment challenge with a relatively high rate of severe complications, including avascular necrosis (AVN), non-union, growth arrest, subsequent deformity, and loss of motion. 24,25 The limited ossification makes it difficult to correctly assess the type of fracture or level of displacement with radiographs alone.…”
Section: Fracture Fixationmentioning
confidence: 99%
“…Arthroscopic-assisted fracture management may be beneficial in other fractures about the elbow (coronoid, radial head/neck, capitellum, supracondylar), and recent small case series and reports have demonstrated good results with regard to fracture union, range of motion and complications. 7,21,28 There is also the potential for arthroscopic corrective osteotomies following supracondylar malunion, in which the current complication rates for open procedures is reported at upwards of 40%. 29 Larger studies and trials are needed, however, to compare these minimally-invasive procedures to their open counterparts.…”
Section: Fracture Fixationmentioning
confidence: 99%